2014
DOI: 10.1177/1352458514541579
|View full text |Cite
|
Sign up to set email alerts
|

Digesting the emerging role for the gut microbiome in central nervous system demyelination

Abstract: Abstract:The fields of microbiology, immunology, neurology and nutrition are rapidly converging, as advanced sequencing and genomics-based methodologies have enabled the mapping out of the microbial diversity of humans for the first time. Bugs, guts, brains and behavior were once believed to be separate domains of clinical practice and research; however, recent observations in our understanding of the microbiome indicate that the boundaries between domains are becoming permeable. This permeability is multidire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 37 publications
0
53
0
Order By: Relevance
“…There are only few reports that address the microbial flora in MS patients and those that do address it, deal with the intestinal microbiota, especially after the discovery of its role in the dysregulation of innate and adaptive immune response, central nervous system demyelination, and the development of inflammatory bowel disease (Hansen 2015;Joscelyn and Kasper 2014;Round and Mazmanian 2009). The gut microbiome in MS patients has been characterized by a microarray analysis of bacterial 16S ribosomal RNA and changes in the abundance of some taxonomic units, including a lower level of Faecalibacterium, have been observed (Cantarel et al 2015).…”
Section: Introductionmentioning
confidence: 97%
“…There are only few reports that address the microbial flora in MS patients and those that do address it, deal with the intestinal microbiota, especially after the discovery of its role in the dysregulation of innate and adaptive immune response, central nervous system demyelination, and the development of inflammatory bowel disease (Hansen 2015;Joscelyn and Kasper 2014;Round and Mazmanian 2009). The gut microbiome in MS patients has been characterized by a microarray analysis of bacterial 16S ribosomal RNA and changes in the abundance of some taxonomic units, including a lower level of Faecalibacterium, have been observed (Cantarel et al 2015).…”
Section: Introductionmentioning
confidence: 97%
“…Infiltration of Th1 and Th17 CD4+ T-cells into the central nervous system seems to be prominent in MS. 4 CD4+ T-regulatory cells protect against autoimmunity by suppressing auto-reactive effector T-cells, and decreased numbers or defective function of T-regulatory cells may also contribute to the development of MS. 4 Environmental factors such as the gut microbiota may contribute to MS immunopathogenesis by directing differentiation of CD4+ T-cell phenotypes or impacting T-regulatory cell function. Previously reviewed animal studies have demonstrated that alteration of the gut microbiota can powerfully modulate immune-mediated demyelination in experimental autoimmune encephalomyelitis (EAE) and paved the way for examination of the gut microbiota in MS. 2,5 The gut microbiome in MS Imbalance, or "dysbiosis" of the gut microbiota, is implicated in numerous diseases, including obesity, diabetes mellitus type 2 (T2DM), diabetes mellitus type 1 (T1DM), inflammatory bowel disease (IBD), and rheumatoid arthritis (RA). 3 Examination of the gut microbiota in MS requires a working understanding of normal human gut microbiota composition.…”
Section: Introductionmentioning
confidence: 99%
“…Composed of approximately 10 14 highly diverse micro-organisms, the gut microbiota is vital to digestion and metabolism. 1 Its immunologic functions, however, including physical blockade of ingested potential pathogens, oral tolerization to antigenic stimuli, and modulation of the gut-associated lymphoid tissue (GALT) may play a significant role in autoimmune diseases such as MS. [1][2][3] Research examining the gut microbiota in MS is framed by our understanding of MS immunopathogenesis. Infiltration of Th1 and Th17 CD4+ T-cells into the central nervous system seems to be prominent in MS. 4 CD4+ T-regulatory cells protect against autoimmunity by suppressing auto-reactive effector T-cells, and decreased numbers or defective function of T-regulatory cells may also contribute to the development of MS. 4 Environmental factors such as the gut microbiota may contribute to MS immunopathogenesis by directing differentiation of CD4+ T-cell phenotypes or impacting T-regulatory cell function.…”
Section: Introductionmentioning
confidence: 99%
“…Such systemic inflammation can alter the macrophage and microglia phenotype in EAE (Moreno et al, 2011), highlighting the relevance of systemic inflammation in the etiology and course of MS. The gut microbiome and gut permeability have recently been proposed to be major contributors to demyelinating disorders, especially MS (Joscelyn and Kasper, 2014). In the EAE model, increased gut permeability is an early event, prior to neurological symptoms, with heightened immuno-inflammatory activity contributing to these gut changes.…”
Section: Depression Gut Permeability Melatonin and Msmentioning
confidence: 99%